Correlation of Periodontal Phenotype with Periodontal Probing Depth in Maxillary Anterior Teeth: A Cross-Sectional Study Using Probe Transparency Method - Maha Maqool; Usman Manzoor; Sadia Iqbal; Sittara Javed; Hania Ali; Zubair Ahmed Khan (Journal of Aziz Fatimah Medical and Dental College)
ABSTRACT